2005
DOI: 10.1071/wf05040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prescribed fire on soil quality in Mediterranean grassland (Prades Mountains, north-east Spain)

Abstract: This study examines the effects of a prescribed fire, conducted in grassland in order to maintain a fire break, on soil quality (pH and nutrients) in the Prades Mountains in the Mediterranean climate of north-east Spain. Soil at a 4 × 18 m study plot, located in an abandoned agricultural terrace on calcareous bedrock at 760 m above sea level, was sampled at 0–5 cm depth at 42 sampling points before, immediately after and one year after the burn and analysed for pH and carbon, nitrogen, potassium and phosphorou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
5
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(76 citation statements)
references
References 12 publications
4
65
5
2
Order By: Relevance
“…In some parts of Europe, mainly in the Mediterranean countries, fuel management techniques have not only been implemented and used, but also the effects of such techniques on trees, forest floor, soil and breeding bird population have been investigated, though not on a very wide scale (e.g. Fernandes and Botelho, 2003;Moreira et al, 2003;Ú beda et al, 2005). Despite being an established practice, it is a technique that is banned in some European countries.…”
Section: Prescribed Burning Overviewmentioning
confidence: 99%
“…In some parts of Europe, mainly in the Mediterranean countries, fuel management techniques have not only been implemented and used, but also the effects of such techniques on trees, forest floor, soil and breeding bird population have been investigated, though not on a very wide scale (e.g. Fernandes and Botelho, 2003;Moreira et al, 2003;Ú beda et al, 2005). Despite being an established practice, it is a technique that is banned in some European countries.…”
Section: Prescribed Burning Overviewmentioning
confidence: 99%
“…Arocena and Opio [10] also reported that soil pH increased by 2 or 3 pH units for two or three years after fires, and Rhoades et al [53] found that soil pH was higher in logged burnout areas for more than three years after combustion of downed logs compared with adjacent soil. Úbeda et al [54] observed that pH returned to pre-fire values just one year after the fire. This increase is generally due to the combustion of organic matter and ash production.…”
Section: Soil Phmentioning
confidence: 99%
“…Despite this, little research has been carried out on soil properties from boreal grassland ecosystems (Pereira et al, 2013a, c). The majority of studies on fire impacts on grassland soils have been carried out in tropical (Coetsee et al, 2010;Michelsen et al, 2004), subhumid (Knapp et al, 1998), desert (Ravi et al, 2009a;Whitford and Steinberger, 2012), arid (Vargas et al, 2012), semiarid (Dangi et al, 2010;Ravi et al, 2009b;Xu and Wan, 2008), temperate (Harris et al, 2007) and Mediterranean environments (Marti-Roura et al, 2013;Novara et al, 2013;Úbeda et al, 2005).…”
Section: Introductionmentioning
confidence: 99%